Strategic Alliances or What Alternative? The Bia Kud Chum and Community Culture in Thailand. Issue 3 (2nd September 2018) - Heis, Alexandra
Abstract: The article gives a basic insight into the different currents that are part of an alternative development paradigm in Thailand. While a global trend of alternatives as reflected in the post-development critique gained momentum in the 1990s, its agents in Thailand have a much longer history. Taking up the critique of post-development approaches as remaining at a discursive level, rather than actually effecting progressive material social change, this article traces the strategic alliances, junctures and disjunctures among alternative development proponents in the north-eastern province of Yasothon. Only a couple of months after the historic financial crisis hit Thailand, and just after the 'Sufficiency Economy Philosophy' – an alternative development paradigm framed by the King – was roughly outlined in December 1997, a small rural community of five villages in the north-eastern district of Kud Chum, with a history of political dissent, started to implement a community currency network. This article suggests that the reactions and dynamics, which the implementation triggered, as well as preceding and subsequent processes of co-optation and collaboration, are very telling in terms of the overall workings of Sufficiency Economy as a political programme. The events tell a story of top-down co-optation, bottom-up strategic alliances, as well as a plethora of other interests and aims on the ground.